Environmental scan on women's health information resources in Ontario, Canada (Information Research: An International Electronic Journal)
This paper describes the development of an environmental scanning system by a group of academics and health librarians for the purpose of conducting a consumer scan on women's health information resources on behalf of Ontario Women's Health Council, Ontario Ministry of Health and Long-Term Care. The focus of this paper is on the use of database technology in information acquisition for environmental scanning.